Peti Koin Bermantra: SDGs Instrument “No Poverty” Fisheries Sector in Wajak District - Rizqi Khafiqi Salzabila Rohmah; Farida Rahmawati; Maulien Khairina Sari (Jambura Equilibrium Journal, 2023)
The Sustainable Development Goals (SDGs) are global action plans agreed upon by world leaders to end poverty, reduce inequality and protect the environment as part of efforts to achieve the national Sustainable Development Goals (SDGs). Ideas related to the current national development model, based on Presidential Regulation No. 59 of 2017, concerning achieving sustainable national development goals. In this regard, the regional government of East Java province has made an acceleration policy in dealing with poverty through the Anti-Poverty Program (APP), which is currently renamed the Peti Koin Bermantra. The research was conducted to determine the program's success in dealing with the problem of poverty in the fisheries sector in The Wajak sub-district through the Mugi Mulya business group as a group of beneficiaries. The research was conducted using the Descriptive Qualitative method, primary data from observations and interviews and secondary data from written documents at the Malang Regency Bappeda. Based on the research conducted, it is known that the program’s sustainability can increase catfish productivity by increasing daily sales by 450% within six years of first receiving assistance. The income of group members also increased, where it was only around Rp. 20,000 before the assistance per day, and gross profit reached Rp after the assistance. 600,000 per day. Based on this, the sustainability of the program can improve the economy of the productive poor, supporting the Sustainable Development Goals “No Poverty”. In the future, it is hoped that the success of the Peti Koin Bermantra program can be felt by various sectors so that it can improve the welfare of the wider community through improvements to the publication of program information itself.